Study on Proteomics-Based Aortic Dissection Molecular Markers Using iTRAQ Combined With Label Free Techniques - Deng, Ting; Liu, Yongguang; Gael, Akindavyi; Fu, Xiaohua; Deng, Xiaofang; Liu, Yunfeng; Wu, Yizhang; Wu, Yingzhi; Wang, Huimin; Deng, Yuying; Lai, Jun; Fu, Qiang (Frontiers in Physiology, 2022)
Background: Aortic dissection refers to separation of aortic media and extension along the long axis to form the true and false chambers of the aortic wall. 65-70% of the patients died of cardiac tamponade, arrhythmia, dissection rupture etc. At present, echocardiography, computed tomography angiography (CTA) etc are the main diagnosis tools for aortic dissection. To date, there is no rapid serum molecular marker that can be used for differential diagnosis and risk assessment. Objectives: To screen serum molecular markers systematically amid aortic dissection and acute coronary syndrome, preliminary identify the pathogenesis of acute aortic dissection. Methods：Related cases were statistically analyzed from the database of Guangdong Province Medical Disputes Coordination Committee from 2013 to 2017. Serum samples were quantified by iTRAQ and Label-free analysis and further validated by Elisa. Aortic tissues were evaluated by immunofluorescence and Western blot for proteins verification. Results： AAD cases ratio accounted for 16.27% in all 150 cardiovascular disputes, 59.26% in all cardiovascular death less than 24 hour and 88.89% in the patients remained undiagnosed at the time of death, 84 proteins (66 and 18 up-and down-regulated respectively) were identified by iTRAQ and 16 proteins (9 and 7 up-and down-regulated respectively) by Label-free. Nine proteins (Lumican、FGL1、PI16、MMP9、FBN1、MMP2、VWF、MMRN1 and PF4) related to the pathogenesis of aortic dissection were identified by David / Ease and String techniques as candidate biomarkers for verification test. Four proteins (Lumican, FGL1, PI16 and MMP9) were found to be statistically different after Elisa verification. The expression of FGL1, PI16, MMP9 proteins was pathologically significantly increased except Lumican. Histologically, TGF-β1, α-SMA and Collagen1 were also significantly higher in aortic group. Conclusion：Lumican, FGL1, PI16 and MMP9 may be potential biomarkers in AAD patients, and Lumican-mediated TGF-β1 pathway is likely to be involved in the pathogenesis of aortic dissection.